KINETICS OF CALCITE PRECIPITATION FROM SEAWATER: II. THE INFLUENCE OF THE IONIC STRENGTH - A CLASSIC CHEMICAL KINETICS DESCRIPTION FOR STRONG ELECTROLYTE SOLUTIONS - Zuddas P.; Mucci A. (My University, 1998)
To characterize the influence of ionic strength on the kinetics of calcite precipitation from seawater solutions we carried out a set of experiments at four different ionic strengths (I = 0.10; 0.34; 0.55; 0.93 m) in NaCl-CaCl2 solutions, at the temperature of 298.15K and a CO2 partial pressure of 100 Pa. The constant addition technique was used in order to maintain [Ca2+] at #10.5 mmol/kg, while the [CO32-] was varied to isolate its role on the precipitation rate of calcite.Assuming that the calcite precipitation in this solution is dominated by the reaction: Ca2++CO32-#kbkf CaCO3 (1) where kf and kb are, respectively, the forward and reverse reaction rate constants, the net precipitation rate, R, can be described at any ionic strength by R=kf (aCa2+)n1(aCO32-)n2-kb (2) or, in its logarithmic form Log (R+kb)=Log Kf+n2 Log [CO32-] (3) where ni are the partial reaction orders with respect to the participating ions, a and γ are, respectively, the ion activities and activity coefficients and, Kf = kf(aCa2+)n1(γCO32-)n2, a constant at a given ionic strength. Results of this study indicate that, when the ionic strength is increased from 0.10 to 0.93 m, the partial reaction order with respect to the CO32- concentration increases from 1 to 3 and the forward reaction rate constant, kf, increases by several orders of magnitude. This is interpreted as both a change in the calcite precipitation mechanism and a catalysis generated by the presence of inert electrolytes. Applying our model to the rate measurements carried out by in seawater solutions at various salinities, under the compositional condition [Ca2+] # [CO32-], we find that the partial reaction order with respect to the carbonate ion and the forward reaction rate constant increase as a function of the total ionic strength of the seawater solutions. A 50% increase of the total ionic strength of the parent solution results in an increase of the precipitation rate by 2 orders of magnitude. Finally, we propose that ion interactions in solution and a concomitant change of the precipitation mechanism may contribute to the development of nonequivalent kink sites of different sizes on the surface of the growing crystal but which still satisfy the symmetry. Variations in the amount of foreign ions adsorbed and incorporated into marine calcites could, therefore, be determined by the density of these less constrained sites, which, in turn, would be dependent on the total ionic strength of the solution.